Analysis of Paragraph Coherence in Students’ Proposal Assignments - Narlianti, Ni Putu Veny; Laba, I Nengah (International Journal of Linguistics and Discourse Analytics, 2026)
This study aims to analyze paragraph coherence in students’ proposal assignments, focusing on cohesion and coherence. It employed a descriptive qualitative approach within the field of linguistics. The data source consists of student proposal documents, while the data consist of paragraphs from the background and literature review sections. Data were collected through documentation, supported by observation and note-taking. Data analysis was conducted through the stages of data reduction, classification, analysis, interpretation, and conclusion drawing. The findings indicate that the level of paragraph coherence in students’ writing is relatively low. Four main forms of incoherence were identified: overly long sentences, weak coherence, unclear references, and excessive repetition. Overly long sentences reduce clarity, while weak coherence is characterized by illogical relationships between ideas. Additionally, the use of unclear references leads to ambiguity, and excessive repetition results in ineffective and monotonous paragraphs. Among these four aspects, coherence problems were found to be the most dominant. The study concludes that students need to improve their ability to construct coherent paragraphs, particularly in developing ideas logically, using references appropriately, and varying lexical elements. Therefore, more focused instruction in academic writing is necessary to enhance the quality of paragraph coherence in proposal writing.